2006
DOI: 10.1115/1.2430719
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Performance of Multipass Parallel and Counter-Cross-Flow Heat Exchangers

Abstract: A thorough study of the thermal performance of multipass parallel cross-flow and counter-cross-flow heat exchangers has been carried out by applying a new numerical procedure. According to this procedure, the heat exchanger is discretized into small elements following the tube-side fluid circuits. Each element is itself a one-pass mixed-unmixed cross-flow heat exchanger. Simulated results have been validated through comparisons to results from analytical solutions for one- to four-pass, parallel cross-flow and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…The e-NTU relationships for multipass parallel cross-flow and multipass counter cross-flow configuration are available from [17][18][19], as shown in Eqs. (2) and (3): For multipass counter cross-flow with N row = 2:…”
Section: Data Reductionmentioning
confidence: 99%
“…The e-NTU relationships for multipass parallel cross-flow and multipass counter cross-flow configuration are available from [17][18][19], as shown in Eqs. (2) and (3): For multipass counter cross-flow with N row = 2:…”
Section: Data Reductionmentioning
confidence: 99%
“…The computation of the important parameters, thermal effectiveness, heat exchanger efficiency and entropy generation, employs the approach delineated in [7,8]. The procedure consists of a sequence of three basic steps: (i) division of the heat exchanger in a finite number of three-dimensional control volumes or elements, each element being itself a mixed-unmixed cross-flow heat exchanger; (ii) solution of the set of governing equations for each element; and (iii) step-by-step solution of the governing equations of subsequent elements along each circuit of the in-tube fluid.…”
Section: Theorymentioning
confidence: 99%
“…9(d) of this reference) was performed. In addition, Cabezas-Gó mez et al [8] have shown that the thermal effectiveness of the complex flow arrangement is higher than that of a four-pass counter-cross-flow heat exchanger with higher values of C * and NTU. However, this result is not suitable to the lower range of C * and NTU, because in this range an opposite trend has been found.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Park and Hrnjak [6] investigated the effect of heat conduction through fins on the capacity of a serpentine gas cooler. Cabezas-Gomez et al [7] proposed a new procedure to evaluate the e-Ntu relation of parallel and counter-cross-flow heat exchangers. Dong et al [8] measured the heat transfer and friction data of flat-tube heat exchangers with wavy fins.…”
Section: Introductionmentioning
confidence: 99%